Beyond "Trimming the Fat": The Sub-editing Stage of Newswriting. (October 2015) - Vandendaele, Astrid; De Cuypere, Ludovic; Van Praet, Ellen
Thus far, professional editing has not been researched extensively in writing research. This article zooms in on sub-editing in newswriting as a form of professional editing, addressing three research questions: (a) What are the ways in which a news article's text is altered?, (b) Are some types of news article altered more significantly than others?, and (c) Are certain news article sections more prone to alterations? Merging the contextualized insights of fieldwork with a corpus-based discourse analytic research perspective, we trace the differences (viz. additions, deletions, translocations, replacements) between the "initial" (right before sub-editing) and "final" (published) version of six different types of news article, (frontpage, headline, long, medium, short, and news wire article) in a corpus sample of 30 broadsheet articles. Our findings are first that—contrary to popular belief that sub-editors mainly "hack away" at news stories, or merely "trim the fat"—additions prevail. Second, we found that most interventions occur in high-stakes articles. Third, we discovered the largest number of interventions in the "entry points" of an article, that is, where—according to eye-tracking research—readers stop scanning and start reading. We discuss our findings in the light of training for professional newswriters.